Floraix: development of an application of flora habitat navigation system in Perak (Floraix) / Muhammad Haziq Azhar and Muhammad Farhan Haqeem Roslan - Azhar, Muhammad Haziq; Roslan, Muhammad Farhan Haqeem (Universiti Teknologi MARA (UiTM), 2024)
The Flora Habitat Navigation Application for Perak is a unique technology for the improvement of the area’s flora and fauna discovering and preserving. Using state-of-the-art geospatial tools and real time collaborative data processing. This application offers maps, plant species descriptions and habitat overviews for Perak’s specific ecological regions. This application integrates Google Maps to provide users with accurate and intuitive route guidance to key flora-rich areas across Perak. By leveraging the robust mapping capabilities of Google Maps, users can easily find and navigate various plant habitats, ensuring a user-friendly experience for both casual explorers and researchers.